Синтез модели и алгоритма управления адаптивного пид-регулятора на основе нечеткой логики с учетом различного типа случайных воздействий - Старов, A. C. (ХНУРЕ, 2012)
The report discusses the synthesis of model and control algorithm of adaptive PID controller based on fuzzy logic functioning of the adapter with the improvement of the quality control system functioning using the pre-emption, which takes into account the different types of random effects.
Keywords: адаптивный пид-регулятор